2021
DOI: 10.21109/kesmas.v16i1.3291
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding History Risk Factor Associated with Stunting of Children Aged 12–23 Months

Abstract: Stunting (low height-for-age) remains a global and national health problem because it increases the risk of disturbances in growth and development and mortality. Banjar Margo District, Tulang Bawang Regency, has the second-highest prevalence in Lampung Province, Indonesia. This study aimed to analyze the association of exclusive breastfeeding history and stunting in children aged 12–23 months in Banjar Margo District. This study used a cross-sectional design on 193 children aged 12–23 months. It was primary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
1
4
0
4
Order By: Relevance
“…Of a sample of 1,459 children under five years, over half (53.8%) were continuously breastfed from birth until their current age (months). This result was similar to the previous studies in that breastfeeding was a preventive factor for reducing childhood stunting (Dabar et al, 2020;Rathaur et al, 2018;Sari et al, 2021). In a mother's breast milk, colostrum, essential nutrients, and vitamins are already included for optimal growth and development of children.…”
Section: Discussionsupporting
confidence: 90%
“…Of a sample of 1,459 children under five years, over half (53.8%) were continuously breastfed from birth until their current age (months). This result was similar to the previous studies in that breastfeeding was a preventive factor for reducing childhood stunting (Dabar et al, 2020;Rathaur et al, 2018;Sari et al, 2021). In a mother's breast milk, colostrum, essential nutrients, and vitamins are already included for optimal growth and development of children.…”
Section: Discussionsupporting
confidence: 90%
“…Hasil penelitian Astuti et al (2020) menunjukkan bahwa ASI eksklusif dapat mencegah stunting. Balita yang tidak diberikan ASI eksklusif akan lebih memiliki risiko stunting sebesar 3,1 kali daripada balita yang diberikan ASI eksklusif (Sari et al, 2021).…”
Section: Hubungan Asi Eksklusif Dengan Kejadian Stuntingunclassified
“…Meanwhile, Amsalu (2008) discovered that children without exclusive breastfeeding were 3.2 times as high risk of malnutrition and 6.9 times as high risk of stunting as children with exclusive breastfeeding. Another study in Banjar Margo District, Tulang Bawang Regency, showed that children without exclusive breastfeeding were 3.1 times as high risk of stunting as those with exclusive breastfeeding (Sari et al, 2021). A study in Mexico also showed that breastfeeding was a consistently protective factor against child stunting (Campos et al, 2020).…”
Section: Discussionmentioning
confidence: 98%